2012
DOI: 10.5433/1679-0359.2012v33n6p2227
|View full text |Cite
|
Sign up to set email alerts
|

Transmissão de fungo entomopatogênico no controle da broca do rizoma

Abstract: ResumoO objetivo deste trabalho foi avaliar a transmissão do fungo entomopatogênico (Beauveria bassiana) entre adultos da broca do rizoma (Cosmopolites sordidus) em condições de campo. Insetos adultos e sadios de C. sordidus foram marcados e liberados na base de touceiras de bananeiras e dois dias após na mesma área foram liberados insetos marcados e inoculados com o fungo B. bassiana. Aos 7, 14, 21 e 28 dias armadilhas de pseudocaule foram utilizadas para a recaptura dos insetos e determinação da mortalidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Dolinski & Lacy (2007) carried out a review on the use of entomopathogens in the control of tropical fruit insects and showed that the control of the banana weevil borer can be performed successfully by using these control agents. López et al (2012), who studied the transmission of the entomopathogenic fungus Beauveria bassiana in the control of C. sordidus, released healthy insects and later insects inoculated with the fungus. When recapturing the insects, they observed an infection rate of 3.7%, characterizing transmission between inoculated and healthy insects due to the increase in the pre-existing natural prevalence, which was only 0.3% of sick insects.…”
Section: Introductionmentioning
confidence: 99%
“…Dolinski & Lacy (2007) carried out a review on the use of entomopathogens in the control of tropical fruit insects and showed that the control of the banana weevil borer can be performed successfully by using these control agents. López et al (2012), who studied the transmission of the entomopathogenic fungus Beauveria bassiana in the control of C. sordidus, released healthy insects and later insects inoculated with the fungus. When recapturing the insects, they observed an infection rate of 3.7%, characterizing transmission between inoculated and healthy insects due to the increase in the pre-existing natural prevalence, which was only 0.3% of sick insects.…”
Section: Introductionmentioning
confidence: 99%